THE NEEDS OF TECHNOLOGY TRANSFORMATION IN FRENCH LITERATURE LEARNING - Dewi, Evi Rosyani; Lustyantie, Ninuk; Isnan, Fathurrahman Nur (IJLECR (International Journal of Language Education and Cultural Review), 2021)
The development of technology has a real impact on the development of education. Education must be able to adapt to be more better, one of which is learning French literature. This study aims to determine learners’ perceptions of the need for technology implementation in French literature learning. This study used a survey method with a qualitative descriptive approach. The findings show that from 90 respondents, 37.9% were strongly agreed, 56.6% were agreed, 5.0% were neutral, 0.1% were disagreed, and 0.3% were strongly disagree with the need for technology implementation in French literature teaching and learning activities. Based on these findings, the implementation of technology is a must and even a necessity in learning French literature